Rhizomes Help the Forage Grass Leymus chinensis to Adapt to the Salt and Alkali Stresses - Xiaoyu Li; Junfeng Wang; Jixiang Lin; Ying Wang; Chunsheng Mu (The Scientific World Journal)
Leymus chinensis has extensive ecological adaptability and can grow well in saline-alkaline soils. The knowledge about tolerance mechanisms of L. chinensis could be base for utilization of saline-alkaline soils and grassland restoration and rebuilding. Two neutral salts (NaCl : Na2SO4 = 9 : 1) and two alkaline salts (NaHCO3 : Na2CO3 = 9 : 1) with concentration of 0, 100, and 200 mmol/L were used to treat potted 35-day-old seedlings with rhizome growth, respectively. After 10 days, the biomass and number of daughter shoots all decreased, with more reduction in alkali than in salt stress. The rhizome biomass reduced more than other organs. The number of daughter shoots from rhizome was more than from tillers. Under both stresses, Na+ contents increased more in rhizome than in other organs; the reduction of K+ content was more in underground than aerial tissue. Anion ions or organic acids were absorbed to neutralize cations. Na+ content in stem and leaf increased markedly in high alkalinity (200 mmol/L), with accumulation of soluble sugar and organic acids sharply. Rhizomes help L. chinensis to adapt to saline and low alkaline stresses by transferring Na+. However, rhizomes lost the ability to prevent Na+ transport to aerial organs under high alkalinity, which led to severe growth inhibition of L. chinensis.